First report on vertebrate coprolites from the Upper Cretaceous (Santonian) Csehbánya Formation of Iharkút, Hungary. (June 2017) - Segesdi, Martin; Botfalvai, Gábor; Bodor, Emese Réka; Ősi, Attila; Buczkó, Krisztina; Dallos, Zsolt; Tokai, Richárd; Földes, Tamás
Abstract: More than 2600 coprolites produced by vertebrates have been found in the fluvial lacustrine beds of the Upper Cretaceous (Santonian) Csehbánya Formation, Iharkút, western Hungary. In this study the mineral components, embedded dietary residues of these coprolites were examined and their ecological significance are discussed. The coprolite assemblage, containing mostly small-sized (length between 0.8 and 8.6 cm) specimens, can be ordered into seven different morphotypes, among which the spiral ones might have been produced by fish with spiral intestinal valves. The surface of the coprolites is mostly smooth and desiccation cracks were observed in only one case, suggesting that most of these coprolites were buried in-situ without long-term subaerial exposure. The fine-grained matrix of coprolites contains small holes, partially digested plant and animal residues but no sedimentary particles. CT-scanning was an effective method for revealing embedded dietary residues despite that the coprolites contain a large amount of pyrite. The coprolites contain cuticle remains, coalified seeds, pollen grains and diatoms. Animal residues may be the evidence of predation: mollusk shell and bone fragments, ganoid scales of Lepisosteiformes fish were frequent and one Pycnodontiformes fish tooth was found as well. It is not possible to ascertain the real producer of the coprolites, but, according to these remains, the Lepisosteiformes and Pycnodontiformes fish were included in the producer's prey. Not only the bone- but also the plant-bearing coprolites are highly phosphatic with mineral apatite in their matrix. However, the embedding fluvial sediment has significantly different chemical composition. The high phosphatic content of coprolites and the apatite might be derived from the carnivorous diet. Plant remains in the phosphatic coprolites may imply an omnivore producer or were the result of their incidental ingestion. Rapid burial and the mineral content of the animal nutriment might have been the responsible factors for the good preservation of the excrements.